2021
DOI: 10.1007/s10643-021-01235-9
|View full text |Cite
|
Sign up to set email alerts
|

Trainee Teachers’ Perceptions of Online Teaching During Field Experience with Young Children

Abstract: The global pandemic of COVID-19 forced trainee teachers from the United Arab Emirates to have virtual field experiences in the field of early childhood education. The various stakeholders, young children, families, preservice teachers, and university faculty hold different perceptions of online teaching formats. The purpose of this study was to examine the perceptions of trainee teachers and faculty supervisors about online field experiences with young children. The study was done using a qualitative case stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 23 publications
(36 reference statements)
1
20
0
Order By: Relevance
“…Similarly, to face-to-face education, managing courses and learning is crucial for teaching effectively in an online environment (Albrahim, 2020). In a recent study conducted with preservice early childhood educators and their university supervisors, the importance of high-quality effective classroom management for successful online teaching and learning in early childhood was underscored by all participants (Mohebi & Meda, 2021). However, the present study indicated that online classroom management was challenging for the participating preservice teachers and acted as a hindering factor for quality during this remote teaching practicum.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Similarly, to face-to-face education, managing courses and learning is crucial for teaching effectively in an online environment (Albrahim, 2020). In a recent study conducted with preservice early childhood educators and their university supervisors, the importance of high-quality effective classroom management for successful online teaching and learning in early childhood was underscored by all participants (Mohebi & Meda, 2021). However, the present study indicated that online classroom management was challenging for the participating preservice teachers and acted as a hindering factor for quality during this remote teaching practicum.…”
Section: Discussionmentioning
confidence: 50%
“…Similarly, Sepulveda-Escobar and Morrison (2020) underlined the important role of the relationships, communication, and care that preservice teachers received from mentor teachers and university supervisors during an online teaching practicum. Thus, collaborative working relationships, communication, and the guidance of other stakeholders should be provided to help preservice teachers learn about distance education and help them gain various pedagogical skills for teaching online (Mohebi & Meda, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, they might be unable to afford data, digital devices, and electronic power fees. With respect to online participation, the repertoire of teacher-educator strategies must be expanded (Mohebi & Meda, 2021 ) to encourage preservice teachers to participate in online classes (Loose & Ryan, 2020 ; Scull et al, 2020 ). Teacher-educators should creatively build flexible spaces where preservice teachers could share and discuss their learning and teaching online.…”
Section: Resultsmentioning
confidence: 99%
“…Only a few studies have discussed the dilemma of online education for preservice teacher education in early-childhood education (Kim, 2020 ; Kinkead-Clark, 2021 ; Mohebi & Meda, 2021 ). Most have focused on the issue in relation to elementary and junior secondary levels, where K–12 students show more self-control and are more aware of the need to follow preservice teachers’ online instructions than children in early-childhood education (Cirillo et al, 2020 ; Clark & Newberry, 2019 ; König et al, 2020 ; Miller & Flint-Stipp, 2019 ).…”
Section: Preservice Early-childhood Teacher Education During the Covi...mentioning
confidence: 99%